2016
DOI: 10.1016/j.bar.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Market reaction to the positiveness of annual report narratives

Abstract: This paper focuses on narratives published by UK companies, defined here as the content of annual reports excluding financial statements and notes to accounts. We endeavour to gauge the tone of these narratives by recording the frequency of positive words appearing in the text. We show that the extent of positiveness is related to market reaction around the disclosure date. This conclusion is maintained even after controlling for the financial figures that are reported simultaneously and company-specific chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 87 publications
7
75
3
3
Order By: Relevance
“…Accordingly, recent accounting and finance research has paid attention to the association of linguistic attributes of corporate reports with corporate behavior and economic outcomes (Biddle, Hilary, & Verdi, 2009;Davis, Piger, & Sedor, 2012;Huang et al, 2014;Larcker & Zakolyukina, 2012;Li, 2008;Rogers, Van Buskirk, & Zechman, 2011). The sentiment (i.e., tone) of messages reflected in annual reports (Henry, 2008;Huang et al, 2014;Yekini, Wisniewski, & Millo, 2016) tends to influence investors' and analysts' views about firms. Similarly, one can argue that annual report tone would be associated with audit risk assessment (see Lopatta, Gloger, & Jaeschke, 2017;Yang, Yu, Liu, & Wu, 2018), as, for example, auditing standards require auditors' perusal of information that accompanies audited financial statements (International Federation of Accountants, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, recent accounting and finance research has paid attention to the association of linguistic attributes of corporate reports with corporate behavior and economic outcomes (Biddle, Hilary, & Verdi, 2009;Davis, Piger, & Sedor, 2012;Huang et al, 2014;Larcker & Zakolyukina, 2012;Li, 2008;Rogers, Van Buskirk, & Zechman, 2011). The sentiment (i.e., tone) of messages reflected in annual reports (Henry, 2008;Huang et al, 2014;Yekini, Wisniewski, & Millo, 2016) tends to influence investors' and analysts' views about firms. Similarly, one can argue that annual report tone would be associated with audit risk assessment (see Lopatta, Gloger, & Jaeschke, 2017;Yang, Yu, Liu, & Wu, 2018), as, for example, auditing standards require auditors' perusal of information that accompanies audited financial statements (International Federation of Accountants, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, financial performance can be examined in relation to managerial behaviour (Merkl-Davies et al, 2011) and the expected reactions of stakeholders (Yekini, Wisniewski, & Yuval, 2016). The necessity of merging qualitative and quantitative assessment is mentioned in the evaluation of all types of firms, financial (Belás, 2012;Todea & Lazar, 2012) and non-financial (Cardinaels & van Veen-Dirks, 2010;Golas & Kurzawa, 2016), although a bias resulting from the subjectivity of the qualitative assessment has been referred to by several authors (Hitz, 2007;Gottdiener, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this respect, Fiss and Zajac's () findings indicate that firms that undertake strategic change elicit positive shareholder reactions when they use a balancing frame in their disclosures, which recognizes the claims of common organizational stakeholders’ in addition to shareholders. Finally, Yekini et al () also found a significant positive association between the degree of positiveness of companies’ annual reports and abnormal returns around disclosure dates. Overall, the literature on corporate disclosures provides an empirical basis for the argument that the use of an affective tone that induces a positive impression of the organization is likely to motivate shareholders to maintain their investment ties.…”
Section: Hypothesis Developmentmentioning
confidence: 91%